Keeping the 'C' in CBPR: Exploring Community Researchers' Experiences with Human Subjects Protection Training Requirements. - Cruz, Naomi; Adams, Christiana; Akhimien, Constance; Allibay Abdulkadir, Fauziyya; Battle, Cherriece; Oluwayemi, Maria; Salimon, Olanike; Lassiter, Teri; Kantor, Leslie (Behavioral Medicine)
Community-engaged research is increasingly recognized for its potential to advance health equity. The ability to conduct such research in the United States is predicated on the completion of human subjects protection courses; however, prior studies suggest that many of these required courses may not adequately accommodate the varied skillsets and backgrounds of community members involved with carrying out research. The present study explores community researchers' (CRs') experiences with a human subjects protection course frequently required by U.S. academic institutions. Six CRs involved in conducting a community-based participatory research (CBPR) project on Black women's pregnancy-related experiences were interviewed about their completion of the required course. Across multiple interviews, CRs noted challenges with the training length, competing external demands, module readability, content relevancy, end-of-module quizzes, and technology requirements. Despite such obstacles, CRs still valued the opportunity to learn and felt more knowledgeable and capable post-course completion. Recommendations for course improvement were explored. University requirements for human subjects protection trainings may place an undue burden on community members preparing to conduct research, impede academic-community partnerships, and discourage the initiation and continuation of community-engaged studies. Course alternatives that are tailored to CRs as well as community-academic partnerships could enhance the feasibility, relevance, and effectiveness of such trainings.